(untitled) (Journal of Human Sciences, 2026)
This research examines the issue of citizenship awareness within the Libyan societal perception and the level of accompanying strategic political awareness. The concept of the “nation” is viewed as the primary incubator of citizenship, as its meanings are reflected in the revitalization of citizenship and the development of its practice. Based on this premise, the study explores the archaeological layers of citizenship awareness within the Libyan collective imagination, within the boundaries of societal consciousness, with a particular focus on the potential for establishing an effective and stable form of citizenship. It also addresses the impact of the residual effects of “place anxiety” on the memory of political action in Libyan society. Furthermore, the research analyzes the factors influencing political action and the deterioration and anxiety it has experienced as a result of multiple transitional phases. This has led to procrastination in political dialogue and the erosion of values of tolerance. Such conditions have manifested in practices of self-flagellation and the breach of commitments, contributing to a setback and fragmentation of political will. Consequently, the values of the nation, in the perception of those residing within it, have become weakened and marginalized. This setback and accompanying negligence underscore the urgent need to restore the values of citizenship through revitalization, renewal, and reinforcement, by means of a dynamic political call that adheres to democratic principles and contributes to strengthening national unity.